Художнє висвітлення міжкультурної українсько-єврейської комунікації у прозі Івана Франка - Колесник, А. В. (My University, 2017)
У статті аналізуються особливості художнього висвітлення у про- зових творах Івана Франка українсько-єврейської міжкультурної комунікації, що відбувалася в суспільстві Галичини кінця XIX- почат- ку XX століття. Розглядаються міжособистісні та міжетнічні взаємовідносини, які представлені в творах І. Франка, та історичні події, що вплинули на художнє відтворення єврейської тематики.
In the article features of artistic depiction of Ukrainian-Jewish intercultural communicatbn in Halycia at the end of XIX- beginning of XX centuries in Ivan Franko's novels are analyzed. Interpersonal and interethnic relatbns, presented in Ivan Franko's novels, and historical events that had influence on artistic reproductbn of Jewish themes are considered. The study of Jewish ploblematics in the artistic heritage of Ivan Franko, which illuminates the sphere of human relationships and the Jewish existence in Galicia, is an important aspect of modem Franko science in Ukraine. Ivan Franko author's perception of Jewish ploblematics is analyzed on the material of Franko's prose, where the problem of intercultural Ukrainian- Jewish relations as a sphere of human relatbns and an important part of Jewish existence in the society of Galicia is highlighted. In the article the representatbn of interpersonal relatbns such as upbringing in Jewish families, environment and family influence on the formatbn of personality, reflected in Franko's prose (novels "Pies With Bilberries", 'To The Light", "Gava") are studied. In the analyzed novels the examples of children's upbringing appear: positive educatbnal guidance and negative situatbns, inappropriate to generally accepted moral standards of parenting, that turns natural abilities into a means of gaining wealth (novel "Pies With Bilberries").
Keywords: єврейська тематика; Іван Франко; міжкультурна комунікація